Labor market participation, political ideology and distributive preferences - Simona Demel; Abigail Barr; Luis Miller; Paloma Ubeda (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
Using a political-frame-free, lab-in-the-field experiment, we investigate the effects of employment status and political ideology on preferences for redistribution. The experiment consists of a real-effort task, followed by a four-player dictator game. In one treatment, initial endowments depend on participants' performance in the real-effort task, i.e., they are earned, in the other, they are randomly determined.We find that being employed or unemployed affects revealed redistributive preferences, while the political ideology of the employed and unemployed does not. In contrast, the revealed redistributive preferences of students are strongly related to their political ideologies. The employed and right-leaning students redistribute earnings less than windfalls, the unemployed and left-leaning students make no such distinction. We conclude that, when people are not exposed to the sometimes harsh realities of the labor market, their redistributive preferences depend on their political ideology but, when they are exposed, the effect of those realities overrules their ideology.
Keywords: 330; economic status; lab-in-the-field experiments; left-right scale; redistribution